Advancing Disaster Risk Finance in Belize - World Bank Group (World Bank, Washington, DC, 2019)
The objective of this report is to make recommendations for the Government of Belize (GoB) for the formulation of a country-specific comprehensive disaster risk finance (DRF) strategy, based on the assessment of the legislative, financial management, fiscal, and insurance market environment in Belize.